Hippocampal atrophy and memory dysfunction associated with physical inactivity in community‐dwelling elderly subjects: The Sefuri study. Issue 2 (29th December 2016) - Hashimoto, Manabu; Araki, Yuko; Takashima, Yuki; Nogami, Kohjiro; Uchino, Akira; Yuzuriha, Takefumi; Yao, Hiroshi
Abstract: Background: Physical inactivity is one of the modifiable risk factors for hippocampal atrophy and Alzheimer's disease. We investigated the relationship between physical activity, hippocampal atrophy, and memory using structural equation modeling (SEM). Materials and Methods: We examined 213 community‐dwelling elderly subjects (99 men and 114 women with a mean age of 68.9 years) without dementia or clinically apparent depression. All participants underwent Mini‐Mental State Examination (MMSE) and Rivermead Behavioral Memory Test (RBMT). Physical activities were assessed with a structured questionnaire. We evaluated the degree of hippocampal atrophy (z‐score—referred to as ZAdvance hereafter), using a free software program—the voxel‐based specific regional analysis system for Alzheimer's disease (VSRAD) based on statistical parametric mapping 8 plus Diffeomorphic Anatomical Registration Through an Exponentiated Lie algebra. Results: Routine magnetic resonance imaging findings were as follows: silent brain infarction, n  = 24 (11.3%); deep white matter lesions, n  = 72 (33.8%); periventricular hyperintensities, n  = 35 (16.4%); and cerebral microbleeds, n  = 14 (6.6%). Path analysis based on SEM indicated that the direct paths from leisure‐time activity to hippocampal atrophy (β = −.18, p  < .01) and from hippocampal atrophy to memory dysfunction (RBMT) (β = −.20, p  < .01) were significant. Direct paths from "hippocampus" gray matter volume to RBMT and MMSE were highly significant, while direct paths from "whole brain" gray matter volume to RBMT and MMSE were not significant. The presented SEM model fit the data reasonably well. Conclusion: Based on the present SEM analysis, we found that hippocampal atrophy was associated with age and leisure‐time physical inactivity, and hippocampal atrophy appeared to cause memory dysfunction, although we are unable to infer a causal or temporal association between hippocampal atrophy and memory dysfunction from the present observational study. Abstract : Physical inactivity is one of the major modifiable risk factors for hippocampal atrophy and Alzheimer's disease. We investigated the relationship between physical activity, hippocampal atrophy, and memory function using structural equation modeling (SEM). We found that hippocampal atrophy was associated with age and leisure‐time physical inactivity, and hippocampal atrophy appeared to cause memory dysfunction.